2000
DOI: 10.1046/j.1365-2427.2000.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of C:P ratios of seston, bacteria, phytoplankton and zooplankton in a deep, mesotrophic lake

Abstract: Summary The C:P ratios of seston, bacteria, phytoplankton and zooplankton were measured twice a week in situ in mesotrophic, large and deep Lake Constance from April to December 1995. Except for zooplankton, a strong seasonality was exhibited with low C:P ratios during P‐enriched early spring conditions and high values during P‐depleted summer conditions. Molar C:P ratios of seston varied between 180:1 and 460:1 demonstrating moderate phosphorus limitation in spring and during the clear‐water phase, and stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 37 publications
7
37
2
Order By: Relevance
“…The P-content of zooplankton found in this study and the estimated molar C:P ratios above confirmed that this community had lower phosphorus levels than most temperate zooplankton (Hessen, 1990;Hessen & Lyche, 1991). In the lake Constance (Germany), for example, the molar C:P ratios for zooplankton range usually between 45 and 65 (Hochstädter, 2000). Even considering the fact that these C:P ratios were not estimated at the species level, the higher values found in the present study can be seen as evidence of the limiting role of phosphorus for zooplankton in Pampulha reservoir.…”
Section: Anovacontrasting
confidence: 61%
See 1 more Smart Citation
“…The P-content of zooplankton found in this study and the estimated molar C:P ratios above confirmed that this community had lower phosphorus levels than most temperate zooplankton (Hessen, 1990;Hessen & Lyche, 1991). In the lake Constance (Germany), for example, the molar C:P ratios for zooplankton range usually between 45 and 65 (Hochstädter, 2000). Even considering the fact that these C:P ratios were not estimated at the species level, the higher values found in the present study can be seen as evidence of the limiting role of phosphorus for zooplankton in Pampulha reservoir.…”
Section: Anovacontrasting
confidence: 61%
“…In the last two decades, experimental and empirical evidence supporting the theory of elemental homeostasis (C, N, and P) in zooplankton have been published (Sterner et al, 1992). This theory is mostly based on the fact that the variation of elemental composition (C, N, and P) found in zooplankton biomass is lower than the variation observed in phytoplankton or seston particles (Hochstädter, 2000). This pattern indicates the possible existence of homeostasis in the elemental composition of zooplankton.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond edibility inferred from morphology, algal food quality was not measured continuously in Lake Constance, which prevented further analyses of this potentially influential factor on bottom-up control of ciliates. However, the share of ciliate species that supplement their algivorous diet with P-rich bacteria or other zooplankton increased from spring to summer, which may be attributed to pronounced Pdepletion in phytoplankton during summer, yielding P-deficiency in purely algivorous consumers (Hochstädter 2000, Gaedke et al 2002. In addition, bacterivores increased relative to algivores during summer as re-oligotrophication progressed: From July to • September the contribution of Cluster 7, which was largely made up of small scuticociliates known to feed mainly on picoplankton (2imek et al 1994, 1995), increased from an average of 0.4% from 1987 to 1993 to 3% in the 5 yr thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…The high phosphorus demand of aquatic bacteria is reflected by their relatively low biomass C:P ratios (8 to 173:1 by moles; Chrzanowski et al 1996, Hochstadter 2000, Vrede et al 2002. In contrast, water-column ratios of DOC:DOP are typically much higher (400 to 800:1 by mol; Hopkinson et al 1997, McKnight et al 1997).…”
Section: Bacterial Metabolism On Different Dom Sourcesmentioning
confidence: 99%
“…However, the predicted values generated from our multiple regression analyses represent unbiased esti- Table 3) declined exponentially with C:P ratio of different DOM sources. Shaded area: range of C:P ratio of aquatic bacterial biomass reported in the literature (Chrzanowski et al 1996, Hochstadter 2000, Vrede et al 2002 Aquat Microb Ecol 39: [107][108][109][110][111][112][113][114][115][116][117][118][119] 2005 mates of BP and BR. A slightly different pattern emerged when we estimated BGE from predicted instead of observed BP and BR.…”
mentioning
confidence: 99%